TOGAF for designing the enterprise architecture of LAZISMU - Fahana, Jefree; Azhari, Ahmad (Bulletin of Social Informatics Theory and Application, 2018)
LAZISMU as an amil zakat institution has an important role in collecting and managing zakat for public welfare. The existence of Law No. 23 of 2011 and the Minister of Religion Regulation No. 333 of 2015 on Guidelines for Granting Permits for the Establishment of Zakat Institutions requires that the management of zakat, infaq, and sadaq (ZIS) funds be transparent, accountable and prioritize professional principles. For this reason, there needs to be support from information systems and information technology to achieve these business goals. Information systems and technology will be utilized optimally if the development is aligned with the business objectives of the organization. Enterprise Architecture (EA) is a bridge to harmonize the business needs of an organization with Information Systems and Information Technology. Enterprise architecture planning at the LAZ has been designed using The Open Group Architecture Framework (TOGAF) with Architecture Development Method (ADM). Data collection is done by interviewing and making direct observations of the organization. Analysis tools used are the Unified Modelling Language (UML) method and the Value Chain method. The results of this study are blue print business architecture, data architecture, application architecture so that it can support the business processes that exist in LAZISMU